Prevalence of temporomandibular disorders in patients with Hashimoto thyroiditis - Grozdinska, Alina; Hofmann, Elisabeth; Schmid, Matthias; Hirschfelder, Ursula (Journal of Orofacial Orthopedics / Fortschritte der Kieferorthopädie, 2018)
OBJECTIVES: Autoimmune thyroid disease (AITD), also known as Hashimoto thyroiditis (HT), is a degenerative inflammatory disease with high prevalence among women and has been associated with fibromyalgia and widespread chronic pain. The goal was to determine the frequency of temporomandibular disorders (TMD) in patients with HT. METHODS: In all, 119 women (age 19-60 years) were divided into a study (52 women diagnosed with HT) and a control (67 healthy individuals, of which 15 were excluded) group. Serum concentrations of thyroid-stimulating hormone (TSH), free triiodothyronine (fT3), free thyroxine (fT4), anti-thyroglobulin (Tg) and anti-thyroid peroxidase (TPO) antibody levels were measured. The temporomandibular jaw and muscles were examined using the German Society of Functional Diagnostics and Therapy guidelines. The Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) was used to assess TMD. Standardized questionnaires, incorporating epidemiological criteria, state and treatment of the thyroid disease, Helkimo Index (HI), and Fonseca Anamnestic Index (FAI), were filled out by all patients. RESULTS: The two groups did not differ in terms of demographic parameters or mandibular jaw mobility. Significantly higher levels of anti-TPO and anti-Tg were attested in all subjects of the HT group. Markedly elevated prevalence of TMD was found in the HT group. Muscle pain and stiffness were found in 45 (86.5%) subjects of the HT group (p < 0.001), of whom 33 (63.4%) also had disc displacement with reposition (p < 0.001). Whereas 50% of the control group showed no TMD symptoms, all subjects in the HT group had symptoms. CONCLUSIONS: A significantly elevated prevalence of TMD was found in patients with HT. Thus, patients with TMD who do not respond to therapy should be referred for thyroid diagnostic workup.
EVALuna2:36411